2003
DOI: 10.1002/ptr.1209
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of saffron (Crocus sativus Linn.) on genotoxins‐induced oxidative stress in Swiss albino mice

Abstract: The modifying effects of the aqueous extract of saffron (dried stigmas of Crocus sativus Linn.) on cisplatin (CIS), cyclophosphamide (CPH), mitomycin-C (MMC) and urethane (URE) induced alterations in lipid peroxidation and antioxidant status were investigated in Swiss albino mice. Three doses of saffron (20, 40 and 80 mg/kg body weight) were orally administered to mice for 5 consecutive days prior to administration of genotoxins. A significant reduction in the extent of lipid peroxidation with a concomitant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 27 publications
2
68
0
5
Order By: Relevance
“…The modifying effects of saffron and its carotenoids on antioxidant enzymatic activities have also been shown in other experimental models (Premkumar et al, 2001;Premkumar et al, 2003;Shen and Qian, 2006). Moreover, crocin and other carotenoids from saffron prevent the death of rat pheochromocytoma (PC-12) cells, apoptotic morphological changes, and DNA fragmentation induced by tumor necrosis factor (TNF)-a and serum=glucose deprivation by its antioxidant effects and increasing GSH synthesis (Soeda et al, 2001;Ochiai et al, 2004aOchiai et al, , 2004bOchiai et al, , 2007.…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 67%
See 2 more Smart Citations
“…The modifying effects of saffron and its carotenoids on antioxidant enzymatic activities have also been shown in other experimental models (Premkumar et al, 2001;Premkumar et al, 2003;Shen and Qian, 2006). Moreover, crocin and other carotenoids from saffron prevent the death of rat pheochromocytoma (PC-12) cells, apoptotic morphological changes, and DNA fragmentation induced by tumor necrosis factor (TNF)-a and serum=glucose deprivation by its antioxidant effects and increasing GSH synthesis (Soeda et al, 2001;Ochiai et al, 2004aOchiai et al, , 2004bOchiai et al, , 2007.…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 67%
“…Radical scavenging, antioxidant activity, and promotion of the diffusivity of oxygen in different tissues were also reported for saffron extract or its bioactive constituents (Rios et al, 1996;Verma and Bordia, 1998;Assimopoulou et al, 2005;Kanakis et al, 2007a). Saffron extract also has chemopreventive and genoprotective effects and protects from genotoxin-induced oxidative stress in mice (Nair et al, 1995;Premkumar et al, 2001;Abdullaev et al, 2002;Premkumar et al, 2003).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…According the free radicals theory, imbalance among pro oxidants and anti-oxidants eventually causes oxidative damages on cellular processes and steroidogenesis in lydic cells (Luo et al, 2006). Based on Premkumar et al (2003) report, saffron due to its carotenoid compounds results in regulating the peroxidase activity of lipids, antioxidants and detoxification. Ochiai et al (2004) have reported that saffron's crocines through indirect increasing of m-RNA enzyme, gamma glotamilsyteienilsyntethaseincrease the restored glutathione amount inside the cell and have a considerable importance in regulating the peroxidase activity of lipids and anti-oxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies have indicated that saffron elevates SOD, CAT and GSH-Px activities and inhibits the lipid peroxidation (Premkumar et al 2003). Recently, it has been reported that safranal, an active content of saffron, treats the cerebral ischemia-reperfusion induced oxidative stress and decreases the increased MDA levels (Hosseinzadeh et al 2005).…”
Section: Discussionmentioning
confidence: 99%